1980
DOI: 10.1002/aic.690260204
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of microemulsions: Combined effects of dispersion entropy of drops and bending energy of surfactant films

Abstract: so that the criterion for smau composition gradients becomes -B ' < < 1 (A61 According to ( A 2 ) the condition (A6) also insures small relative pressure gradients. To examine the conditions under which ( A 6 ) is valid, we take the following example: T = 800"K, R, = 50 pm, €4 = 0.015, weight loss = 20% in 10 s (half of which is gases and half is tar). Using molecular weights MG = 25, MT = 250 and coal particle density 1.2 g/cm3, we compute YG = 4.8 x gmols/cm%, YT = 0.48 x 10-4 gmols/ cm%, DGK = 2.74 a$/,, DT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…So, the model can be used to explain qualitatively the alcohol effect on microemulsion stability, and the salt effect, in the extent of modifications of partition constants initiated by adding salt in water. Furthermore, it can be used as a starting point to describe the composition of pseudo phases that lead to stable dispersed systems (microemulsions) before working up stability theories already published [19][20][21] …”
Section: Resultsmentioning
confidence: 99%
“…So, the model can be used to explain qualitatively the alcohol effect on microemulsion stability, and the salt effect, in the extent of modifications of partition constants initiated by adding salt in water. Furthermore, it can be used as a starting point to describe the composition of pseudo phases that lead to stable dispersed systems (microemulsions) before working up stability theories already published [19][20][21] …”
Section: Resultsmentioning
confidence: 99%
“…Two structures are compatible with a zero average curva- Equations [26] and [27] provide some information about g and C. The two are plotted in Figs. 1 and 2, which show that g is small.…”
Section: Allow the Calculation Of The An Equation For The Entropy Of mentioning
confidence: 99%
“…In particular, it was demonstrated that the systems of interest for extraction, i.e. water in oil microemulsions in equilibrium with an excess phase, are governed by the bending stress of the interfacial film (64,65). In spite of their often being only theoretical, these approaches give a good understanding of the factors characterizing the reversed micellar phase, such as the size of the micelles.…”
Section: Thermodynamic Models Of Solubilization In Reversed Micellesmentioning
confidence: 99%